Algoritmo de escalonamento utilizando modelo de Ising com campo externo - Duarte, Nilton Guedes (2019)
Shared medium access algorithms for wireless networks that take into account the link queue size have recently received a lot of attention. In this paper, we propose a distributed algorithm for link scheduling based on Ising’s physical model for antiferromagnetism. This model was adapted, by another work, to consider the size of the queues and to use Glauber dynamics to minimize the energy captured by the model. In this work, we propose the inclusion of the external field of the Ising model to avoid that the algorithm get stuck in local minima of the energy function. In addition, a second algorithm is proposed to transform the result obtained by the model into a viable scheduling. The results demonstrate a good performance in controlling the queues sizes in comparison to the existing algorithms.